Business Development through Literacy-Based Digital Financial Services for Agribusiness Microfinance Institutions - Moch Panji Agung Saputra; Rabiu Hamisu Kankarofi; Fahmi Sidiq (International Journal of Ethno-Sciences and Education Research, 2023)
The agricultural sector plays an important role for the welfare of society. Agriculture plays a role as a producer of food, employment, and a source of foreign exchange for the country. However, the Indonesian agricultural sector still has several problems, namely: 1) Farming capital; 2) Agricultural technology tools; and 3) Marketing of agricultural products. In this regard, one solution that can solve the problem jointly is the existence of an Agribusiness Micro Finance Institution or also known as Lembaga Keuangan Mikro Agribisnis (LKM-A) in Indonesian. LKM-A is a liaison for the easy access of agricultural businesses to various productive resources, namely: capital, technology, and marketing. Along with the role of helping the farming community, there are also several problems faced by LKM-A itself. LKM-A has three main problems, namely 1) LKM-A's limited income because it only pivots on one business scheme, namely members' savings and loans; 2) The management system is still conventional due to lack of access to technology; and 3) Financial services from LKM-A are still limited and conventional. Therefore, this study aims to solve the LKM-A problem. Solutions as problem solvers that will be implemented in this study through theoretical and practical assistance (guidance and training) consist of: 1) Developing business schemes to increase LKM-A income and member welfare, through farming capital financing schemes, agricultural technology rental services, and digital-based marketing of agricultural products; 2) Develop digital-based business management using several supporting systems such as the Database Management System (DBMS), Microsoft outlook, google spreadsheet, and Enterprise Resource Planning (ERP); 3) Develop digital financial system-based business services with digital payments through chip-based E-Money, fintech E-wallet, EDC, and QRis.